Microstructural Anomalies Evaluated by Neurite Orientation Dispersion and Density Imaging Are Related to Deficits in Facial Emotional Recognition via Perceptual‐Binding Difficulties in Autism Spectrum Disorder. Issue 5 (12th February 2020) - Yasuno, Fumihiko; Makinodan, Manabu; Takahashi, Masato; Matsuoka, Kiwamu; Yoshikawa, Hiroaki; Kitamura, Soichiro; Ishida, Rio; Kishimoto, Naoko; Miyasaka, Toshiteru; Kichikawa, Kimihiko; Kishimoto, Toshifumi
Abstract : The integration of visual features is important for recognizing objects as a coherent whole, a key domain of difficulty in autism spectrum disorder (ASD). We tested the hypothesis that ASD patients exhibit difficulties in facial emotional recognition via perceptual binding difficulties due to weak coherence. We assessed 18 ASD and 27 typically developing individuals for their ability to identify emotional expressions from faces in pictures moving behind a narrow vertical and horizontal slit. In this task, only a single local piece of facial information was provided at any one time through the slit. Using a voxel‐based analysis of neurite‐orientation dispersion and density imaging (NODDI), we examined the relationship between NODDI index values at each voxel and the behavioral performance of ASD patients in the slit‐viewing paradigm. ASD patients demonstrated impaired recognition of facial emotional expression only in horizontal slit‐viewing. This deficit was associated with deficits in communication ability. Voxel‐based analysis revealed significant negative correlations between behavioral deficits in horizontal slit‐viewing and NODDI index values in clusters including the ventral occipital complex region, superior temporal/parietal association areas, and forceps major of the corpus callosum. Our results indicated deficits for the first time in perceptual integration of facial expression across hemispheres in ASD patients due to microstructural disturbances in the corpus callosum and areas related to viewing of the human face. This may underscore the difficulties faced by ASD patients in understanding the emotions of other people, contributing to impairments in communication ability in ASD patients. Autism Res 2020, 13: 729–740 . © 2020 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: We assessed ASD and typically developing individuals for their ability to identify emotional expressions from faces in pictures moving behind a narrow vertical and horizontal slit. ASD patients demonstrated impaired recognition of facial emotional expression only in horizontal slit‐viewing. Voxel‐based analysis revealed significant negative correlations between behavioral deficits and NODDI index values in clusters including the corpus callosum. Our results indicated deficits in perceptual integration of facial expression across hemispheres in ASD patients potentially resulting from microstructural disturbances.